Debranching abdominal aortic hybrid surgery for aortic diseases involving the visceral arteries - Ma, Xiantao; Feng, Yi; Tardzenyuy, Mbenkum Achiri; Qin, Bo; Zhu, Qiangzhang; Akilu, Wajeehullahi; Li, Shiliang; Wei, Xiang; Feng, Xiang; Cheng, Cai (Frontiers in Cardiovascular Medicine, 2023)
Objective Aortic diseases involving branches of the visceral arteries mainly include thoracoabdominal aortic aneurysm (TAAA), aortic dissection (AD) and abdominal aortic aneurysm (AAA). The focus of treatment is to reconstruct the splanchnic arteries and restore blood supply to the organs. Commonly used methods include thoracoabdominal aortic replacement, thoracic endovascular aortic repair and hybrid approaches. Hybrid surgery for aortic disease involving the visceral arteries, consisting of visceral aortic debranching with retrograde revascularization of the celiac trunk and renal arteries and using stent grafts, has been previously described and may be considered particularly appealing in high-risk patients. This study retrospectively analyzed recorded data of patients and contrasted the outcomes with those of a similar group of patients who underwent conventional open repair surgery. Methods Between 2019 and 2022, 72 patients (52 men) with an average age of 61.57 ± 8.66 years (range, 36–79 years) underwent one-stage debranching abdominal aortic hybrid surgery. These patients, the hybrid group, underwent preoperative Computed Tomographic Angiography (CTA) and had been diagnosed with aortic disease (aneurysm or dissection) involving the visceral arteries and were at high risk for open repair. The criteria used to define these patients as high-risk group who are in the need of hybrid treatment were American Society of Anesthesiologists (ASA) class 3 or 4. In all cases, we accomplished total visceral aortic debranching through a previous visceral artery retrograde revascularization with synthetic grafts (customized Y or four-bifurcated grafts), and aortic endovascular repair with one of two different commercially produced stent grafts (Medtronic® and Lifetech®). In some cases, we chose to connect the renal artery to the artificial vessel with a stent graft (Viabahn) and partly or totally anastomosed. We analyzed the results and compared the outcomes of the hybrid group with those of a similar group of 46 patients (36 men) with an average age 54.15 ± 12.12 years (range, 32–76). These 46 patients, the conventional open group, were selected for having had thoracoabdominal aortic replacement between 2019 and 2022. Results In the hybrid group, 72 visceral bypasses were completed, and endovascular repair was successful in all cases. No intraoperative deaths occurred. Perioperative mortality was 2.78%, and perioperative morbidity was 9.72% (renal insufficiency in 1, unilateral renal infarction in 5, Intestinal ischemia in 1). At 1-month postoperative CTA showed 2 endoleaks, one of which was intervened. At follow-up, there were unplanned reoperation rate of 4.29% and 5 (7.14%) deaths. The remaining patients’ grafts were patent at postoperative CTA and no endoleak or stent graft migration had occurred. In the conventional open group, 1 died intraoperatively, 4 died perioperatively, perioperative mortality was 10.87% and complications were respiratory failure in 5, intestinal paralysis/necrosis in 4, renal insufficiency in 17, and paraplegia in 2. At follow-up, 5 (12.20%) patients presented with synthetic grafts hematoma 4 (9.76%) patient died, and 6 (14.63%) patients required unplanned reoperation intervention. Conclusion Hybrid surgery is technically feasible in selected cases. For aortic diseases involving the visceral arteries, the application of hybrid abdominal aorta debranching can simplify the operation process, decrease the risks of mortality and morbidity in high-risk and high-age populations and decrease the incidence of various complications while achieving ideal early clinical efficacy. However, a larger series is required for valid statistical comparisons, and longer follow-ups are necessary to evaluate the long-term efficacy of hybrid surgery.